1998
DOI: 10.1073/pnas.95.1.150
|View full text |Cite
|
Sign up to set email alerts
|

Sphingoid base 1-phosphate phosphatase: A key regulator of sphingolipid metabolism and stress response

Abstract: The sphingolipid metabolites ceramide and sphingosine-1-phosphate are second messengers with opposing roles in mammalian cell growth arrest and survival; their relative cellular level has been proposed to be a rheostat that determines the fate of cells. This report demonstrates that this rheostat is an evolutionarily conserved stress-regulatory mechanism that inf luences growth and survival of yeast. Although the role of sphingosine-1-phosphate in yeast was not previously examined, accumulation of ceramide has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
210
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(218 citation statements)
references
References 35 publications
8
210
0
Order By: Relevance
“…Moreover, mutant lag1⌬lac1⌬ cells also have problems surviving at 37°C or after heat shock (unpublished results). Until now, it was claimed that only the sphingoid bases and their phosphorylated counterparts are required for the full heat shock response in yeast (Mandala et al, 1998;Skrzypek et al, 1999). From our results it is conceivable that ceramide is also necessary for survival under these stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mutant lag1⌬lac1⌬ cells also have problems surviving at 37°C or after heat shock (unpublished results). Until now, it was claimed that only the sphingoid bases and their phosphorylated counterparts are required for the full heat shock response in yeast (Mandala et al, 1998;Skrzypek et al, 1999). From our results it is conceivable that ceramide is also necessary for survival under these stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an accumulation of PHS and DHS-1P was observed. It has been shown that exogenous DHS is first phosphorylated upon uptake by the long-chain base kinases Lcb4p and Lcb5p (Nagiec et al, 1998) and then dephosphorylated by Ysr2p or Ysr3p before it can be efficiently converted to ceramide or PHS (Mao et al, 1997;Mandala et al, 1998; see also Figure 1). From our [ 3 H]DHS labeling, the phosphorylation of sphingoid bases and the subsequent dephosphorylation appears to be unaltered because lag1⌬lac1⌬ cells exhibited wild-type amounts of DHS-1P and accumulated PHS.…”
Section: The Lag1⌬lac1⌬ Strain Has a Strongly Reduced Level Of Sphingmentioning
confidence: 99%
“…This e ect is stereospeci®c as an analog of the natural precursor for ceramide, dihydroceramide, fails to induce apoptosis. Recent work has also implicated a role for sphingolipids including ceramides in signaling the heat shock response in yeast (Dickson et al, 1997;Jenkins et al, 1997;Mandala et al, 1998;Wells et al, 1998). In this regard, mutants incapable of rapid synthesis of sphingolipids in response to heat (Figure 2) fail to develop the capacity to grow at elevated temperatures.…”
Section: Ceramide As a Stress Response Signalmentioning
confidence: 99%
“…Interestingly, in Saccharomyces cerevisiae, the homolog of SPP1 has been shown to be a key regulator of stress responses. 12,13 Because previous studies have shown that SPP1 also has a key role in the regulation of the relative levels of S1P and ceramide and thus cell fate, 14 it was important to examine its function in regulating autophagic responses leading to cell survival or cell death. Our results suggest that SPP1, by its influence on intracellular S1P levels, regulates the unfolded protein response (UPR) and ER stress-induced autophagy.…”
mentioning
confidence: 99%